Cell surface MHC-I molecules in dendritic cells undergo fast recycling but do not replenish the Rab11+Arf6+ juxtanuclear compartment to support cross-presentation. (October 2022) - Montealegre, Sebastian; de Kanter, Anne-Floor; Abramova, Anastasia; van Endert, Peter
Abstract : Cross-presentation of internalized antigens by MHC class I molecules (MHC-I) plays a critical role in priming of cytotoxic T cells, recognizing pathogens and tumors. It is thought that peptides derived from cross-presented antigens can be loaded on MHC I in the endoplasmic reticulum as well as in endocytic or phagocytic compartments of murine dendritic cells (DCs). However, the origin of MHC I in the latter compartments is poorly understood. Recently MHC-I trafficking through a juxtanuclear Rab11+ recycling compartment has been suggested to be required for cross-presentation of phagocytosed antigens. We have critically examined the existence of MHC I recycling and the role of Arf6, described to regulate recycling in non-professional antigen presenting cells, in DCs. We confirm fully conformed MHC I accumulation in a juxtanuclear Rab11+ compartment and localize Arf6 to this compartment. DC MHC I molecules undergo fast recycling, however, both fully conformed and "open" internalized MHC I fail to enter a putative slow recycling pathway to the Rab11+Arf6+ compartment. Arf6 knockdown increases cell surface class I density and reduces degradation of internalized "open" MHC I but does not affect fast MHC-I recycling. Moreover, it compromises cross-presentation of antigen internalized via Fc receptors but not other antigens. In conclusion, we demonstrate fast recycling of MHC I in mouse DCs but find that recycling is not required for general cross-presentation. We propose that Rab11 and Rab22, previously reported to be required for cross-presentation, mediate delivery of MHC I from the juxtanuclear compartment to phagosomes/endosomes. However, the origin of the MHC I molecules in this compartment remains to be determined.